Since y = 5x-1, we can fill it into 3x + 3y = -3. First, let's look at relating to a simpler equation. Let's say that x + y = 9 and y = 3 + 5. Now, we can fill it in to get that x + (3 + 5) = 9. Now, we know that 3+5 is 8, so x + 8 = 9. Now, x = 1. Likewise, we can do the same. For 3x + 3y = -3, all we need to do is to switch the y in 3x + 3y = -3 with 5x - 1. So it would become 3x + 3(5x - 1) = -3. Now we distribute to get 3x + 15x - 3 = -3. Now add three to both sides to get 3x + 15x = 0. Now simplify to get 18x = 0. Now we know that x = 0. Now fill x into y = 5x - 1. So y = 5(0) - 1. Now we know that y = -1.
To check fill in the answer to 3x + 3y = -3.
3(0) + 3(-1) = -3
0 + (-3) = -3
0 - 3 = -3
-3 = -3
Now that our check is completed we now know that x is 0 and y is -1.
Answer:
451
Step-by-step explanation:
Answer:
D)
Step-by-step explanation:
i got it corect on the test
Answer:
The dependent variable is number of calories burnt.
Step-by-step explanation:
The dependent variable of an experiment is the variable under study, i.e. it is the variable that is being observed for any changes, when the other variables are changed.
The independent variable is the variable that is being altered to observe the changes in the dependent variable.
A dependent variable can be affected by one or more than one independent variables.
In this case, the data provided represents the number of calories Maggie burned based on the number of miles she ran.
So, the amount of calories burnt is dependent upon the number of miles covered running.
So, the dependent variable is the number of calories burnt and the independent variable is the number of miles she run.
Thus, the dependent variable is number of calories burnt.
Answer:
45
good luck i think this is correct